Proces opravy dvojkolí - Vaculík, František (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2011)
Diplomová práce ve své teoretické části popisuje jednotlivé typy železničních dvojkolí používaných na tuzemských železničních kolejových vozidlech, jejich součásti a postupy montáže. Praktická část popisuje pracoviště kolovky v opravárenském podniku DPOV, a.s. PSO Nymburk, jeho vybavení a výrobní možnosti při kompletní opravě dvojkolí. Praktickou část uzavírají jednotlivé protokoly s výsledky měření dvojkolí.

Diploma work describes in its theoretical part particular types of pairs of wheels used on railway vehicles in Czech Republic as well as their components and assembly instructions. Practical part describes workplace for wheels in reparation DPOV, a.s. at repairing centre Nymburk, its facilities and repairing possibilities by total repair of pairs of wheels. Practical part brings at the end particular report with results of pairs of wheels measuring.
The Process of Repair Vheel Set
Keywords: Dvojkolí; celistvé kolo; obručové kolo; náprava; lisovací diagram; …; Pair of wheels; monoblock wheel; tyred wheel; axle; pressing curve; …